Mapping of Brazilian dissertations and theses: action research and the formation of Mathematics teachers (Revista BOEM, 2025)
This article aims at representing the mapping developed by researching Brazilian dissertations and theses that are available electronically in the Brazilian Digital Library of Theses and Dissertations (BDTD) of the Brazilian Institute of Information in Science and Technology (IBICT) from 2010 to 2020, delimiting the search focusing on teacher training in Mathematics and action research.The general objective of this research was to analyze dissertations and theses produced in the country, analyzing teachers’ training processes in Mathematics and action research. This research is characterized by a qualitative approach, with document search as its specific type. By mapping the database indicated a total of forty-two studies in this area, which were analyzed using content analysis. As a result, the action-research that were used in Brazilian dissertations and theses are still polarized in the South and Southeast, but are rarely present in research on the initial or continuing training of mathematics teachers in Early Childhood Education, Youth and Adult Education, as well as, in Special Education. We emphasise the importance of continue researching and using action research to develop research into teachers’ training in mathematics.
Keywords: action research; teachers’ training; mapping